APATHY: HOW YOUTUBE’S ALGORITHMS FOSTER BINGE-WATCHING BEHAVIOUR - Ахмеров, Андрій (SWorldJournal, 2025)
Our work examines the mechanisms of formation of severe symptoms of psychological dependence on content in YouTube consumers. A technical and psychological analysis of the YouTube platform recommendation algorithm was conducted in order to predict trends